2008
DOI: 10.1002/apj.176
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐induced degradation of nitrosamines trapped in zeolites

Abstract: A new method is reported for the degradation of nitrosamines trapped by zeolites. Significant amount of N -nitrosodiphenylamine (NDPA) in dichloromethane solution, up to one-third, could be degraded by microwave within 1 min once they were adsorbed by zeolite. The nitrosamine molecule, resulting from the electrostatic interaction between the N-NO group of NDPA and the cation of zeolite, could be partially anchored inside the channel of zeolite depending on the degree of structure matching between the adsorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A limited number of studies on mitigating the risk of nitrosamines in tobacco and tobacco smoke have shown that these compounds could be decomposed by microwave treatment (Xu et al, 2008;Gao et al, 2009). Up to one-third of the N-nitrosodiphenylamine sorbed (from dichloromethane solution) on mesoporous siliceous SBA-15 containing 10% CuO degraded after being irradiated by 1000 W microwave for 45 s (Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies on mitigating the risk of nitrosamines in tobacco and tobacco smoke have shown that these compounds could be decomposed by microwave treatment (Xu et al, 2008;Gao et al, 2009). Up to one-third of the N-nitrosodiphenylamine sorbed (from dichloromethane solution) on mesoporous siliceous SBA-15 containing 10% CuO degraded after being irradiated by 1000 W microwave for 45 s (Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Up to one-third of the N-nitrosodiphenylamine sorbed (from dichloromethane solution) on mesoporous siliceous SBA-15 containing 10% CuO degraded after being irradiated by 1000 W microwave for 45 s (Xu et al, 2008). Irradiation of cigarettes sealed in its packaging by microwave (1000 W) for 90 s reduced the contents of nitrosamines in the tobacco and mainstream smoke by 25e30 and 50e60%, respectively (Gao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…9.20 , Xu et al 2008 ). N -Nitrosodiphenylamine (NDPA) is a possible cancer-causing substance in humans, its N-NO bond in molecule is relatively a weak one with the bond energy of 11 kcal mol −1 .…”
Section: Fig 919mentioning
confidence: 99%
“…Microwave‐assisted technology is preferred because of its low time and energy consumption properties, forming an advantage in many fields, such as extraction,1–8 synthesis,8–13 degradation,14–17, and drying18 of some materials. The extraction of functional component from natural plant is one of the important processing technologies in the development and further practical application of plant products.…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus slices, one kind of traditional Chinese Medicine Herb (CMH), is a species of stem and root medicinal herb with the widely curative effects. Moreover, microwave‐assisted technique has been confirmed to be helpful for the synthesis9–13 or degradation14 of some inorganic compound materials. Some researchers also presented that under the condition of very dilute acid, microwave radiation could affect the agglomeration status of some organic polymer, including the hydrolyzation of plant seed gums,15 methylated monosaccharine,16 and hyaluronan (HA) 17…”
Section: Introductionmentioning
confidence: 99%